FABP4 as a key determinant of metastatic potential of ovarian cancer - Gharpure, Kshipra M.; Pradeep, Sunila; Sans, Marta; Rupaimoole, Rajesha; Ivan, Cristina; Wu, Sherry Y.; Bayraktar, Emine; Nagaraja, Archana S.; Mangala, Lingegowda S.; Zhang, Xinna; Haemmerle, Monika; Hu, Wei; et al. (Nature communications, 2018)
The standard treatment for high-grade serous ovarian cancer is primary debulking surgery followed by chemotherapy. The extent of metastasis and invasive potential of lesions can influence the outcome of these primary surgeries. Here, we explored the underlying mechanisms that could increase metastatic potential in ovarian cancer. We discovered that FABP4 (fatty acid binding protein) can substantially increase the metastatic potential of cancer cells. We also found that miR-409-3p regulates FABP4 in ovarian cancer cells and that hypoxia decreases miR-409-3p levels. Treatment with DOPC nanoliposomes containing either miR-409-3p mimic or FABP4 siRNA inhibited tumor progression in mouse models. With RPPA and metabolite arrays, we found that FABP4 regulates pathways associated with metastasis and affects metabolic pathways in ovarian cancer cells. Collectively, these findings demonstrate that FABP4 is functionally responsible for aggressive patterns of disease that likely contribute to poor prognosis in ovarian cancer. In ovarian cancer, metastatic phenotype may impact surgical outcomes. Here, the authors show miR-409-3p regulates FABP4 which can increase metastatic potential of ovarian cancer, and treatment with DOPC nanoliposomes containing either miR-409--3p mimic or FABP4 siRNA inhibits tumor progression in mice.